2011
DOI: 10.1258/jms.2011.011043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neonatal screening results by HPLC and the number of α-thalassaemia gene mutations; consequences for the cut-off value

Abstract: Objectives To evaluate the relationship between FAST peak percentage by adapted Bio-Rad Vnbs analysis using the valley-to-valley integration and genotypes with the aim to improve differentiation between severe a-thalassaemia forms (HbH disease) and the milder disease types. Method DNA analysis for a-thalassaemia was performed on 91 dried blood spot samples presenting normal and elevated FAST peak levels, selected during three years of Dutch national newborn screening. Results Significant differences were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Automation of the first step of SCD neonatal screening offers high throughput with full traceability, a high degree of reproducibility, sensitivity, and a low limit of detection . Precise measurement of Hb fractions in SCD NBS has recently been taken into account mainly in relation to the quantification of Hb Barts in order to discriminate between HbH disease and minor alpha thalassemia . However, to the best of our knowledge, no studies have been carried out to standardize the quantitative interpretation of the different hemoglobin percentages routinely analyzed by HPLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automation of the first step of SCD neonatal screening offers high throughput with full traceability, a high degree of reproducibility, sensitivity, and a low limit of detection . Precise measurement of Hb fractions in SCD NBS has recently been taken into account mainly in relation to the quantification of Hb Barts in order to discriminate between HbH disease and minor alpha thalassemia . However, to the best of our knowledge, no studies have been carried out to standardize the quantitative interpretation of the different hemoglobin percentages routinely analyzed by HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…10 Precise measurement of Hb fractions in SCD NBS has recently been taken into account mainly in relation to the quantification of Hb Barts in order to discriminate between HbH disease and minor alpha thalassemia. 11,12 However, to the best of our knowledge, no studies have been carried out to standardize the quantitative interpretation of the different hemoglobin percentages routinely analyzed by HPLC. For this purpose, we needed to determine normal values and establish optimum cutoff values that could be used routinely in NBS.…”
Section: Discussionmentioning
confidence: 99%
“…Bouva et al 1 found that the percentage haemoglobin Bart's (HbBart's), as depicted by the FAST peak, was only a relative indication for the number of a genes affected in a-thalassaemia. No significant difference was demonstrated between HPLC in 2a/aa and 2a/2a, between 2a/2a and --/aa or between --/aa and --/2a genotypes.…”
mentioning
confidence: 99%
“…In our hands, using the Vnbs system, the percentage HbF ('total F') is calculated by adding the F1 peak percentage with the F peak percentage. To determine the effect of the new gradient, we re-analysed the samples from our previous paper 2 with both method 1.08 (old) and 1.013 (new). We also analysed 186 random fresh samples of the routine screening programme, using both methods.…”
Section: Goodness Et Almentioning
confidence: 99%